Eksplorasi Dilema Etis terhadap Auditor Internal Pemerintahan - Mahardika, Yudhistira; Gede Putu Banu Astawa, Banu (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aimed to explore the ethical dilemmas faced by internal government auditors, particularly those working in a regional inspectorate in Bali. The identity of the research location was deliberately anonymised to protect the privacy of the institution and participants. The study used a qualitative approach with a phenomenological design, allowing the researcher to understand the auditors' real experiences. Data were collected through in-depth interviews, direct observation, and documentation. The findings reveal that auditors often face ethical conflicts due to pressure from superiors and the presence of personal or political interests. These pressures reduce their independence and objectivity when performing audits. As a result, the audit reports they produce become less reliable and do not fully reflect the actual financial conditions. Auditors also struggle with limited human resources and unclear rotation policies, which increase the risk of ethical dilemmas. This study concludes that ethical dilemmas continue to affect the quality of audit reports. It also finds that institutional independence remains fragile. Therefore, continuous ethical training and structural reforms are essential. Strengthening the professional judgement and independence of auditors is crucial to ensuring high-quality audit outcomes and supporting better public sector governance.